Education Equity For The Remote, Disadvantaged Youth: Acceleration Of The Human Capital Development In NTB - Mahurni Mahurni (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2024)
Indonesia's youth hold promise for economic growth, but disadvantaged youth in West Nusa Tenggara (NTB) face hurdles in education and employment. It is not surprising if the NTB's Human Development Index (HDI) lags the national average, reflecting educational shortcomings. There are still many youths lack access to quality education and often lack undergraduate degrees due to language barriers. While scholarship programs like Bidikmisi exist, financial limitations discourage participation, the NTB government's Beasiswa NTB program offers financial aid, but resource constraints limit its reach and scholarship amounts. Fact shows enrolment rates in higher education are significantly lower in rural areas and for less affluent youth. Thus, the NTB government acknowledges these disparities but needs further action to address them. This is a qualitative research examining the NTB government's strategies through a self-administered survey and document analysis. Findings depict that there are two key programs; Beasiswa NTB, which supports high-achieving students domestically and internationally, and Rumah Bahasa, which offers language training, particularly English, to increase access to international scholarships. The government can address these disparities through targeted programs, scholarships, mentorship, and collaboration with NGOs and private entities. The NTB government collaborates with universities abroad through shared funding to support disadvantaged students. Limited funding, reaching remote areas, and ensuring adequate financial support are challenges for the NTB government. While NTB’s scholarship programs and collaborations promote educational equity, further efforts are required to bridge the gap and empower disadvantaged youth.